Evaluating the anti-plaque efficacy of Cymenol mouthwash: A randomized control study - Badi, Hemamanvi; Gummadi, Anusha; Gorle, Santhi; Dalli , Bharath Simha Reddy; Nimmala, Sriram Naidu; Nandipati, Sowmya Reddy (International Journal of Dental Materials, 2025)
Background: Essential Oils (EOs) show strong potential in managing plaque and gingivitis, offering an effective and well-tolerated alternative to chlorohexidine (CHX). Formulations like Listerine, which contain thymol, eucalyptol, menthol, and methyl salicylate, have demonstrated notable plaque-reducing and anti-gingivitis effects with comparatively lower cytotoxicity than CHX. Among Eos, Cymenol (o-cymen-5-ol), a phenolic derivative of isopropyl cresol, exhibits antimicrobial activity primarily by disrupting bacterial cell walls and increasing membrane permeability. Aim: To assess the antiplaque efficacy of a new mouthwash (GingiLacer) containing Cymenol and Zinc chloride as active ingredients. Materials and methods: Thirty participants were enrolled in the study, and their baseline plaque and gingival index scores were documented following the application of an alpha two-tone solution on the teeth. All the subjects were allotted into 2 groups: 15 in Group A, which received Cymenol mouthwash and 15 in Group B, which received Listerine mouthwash after undergoing scaling. Participants were instructed to avoid any additional oral hygiene practices. On days 0 and 14, the alpha two-tone solution was applied to the teeth to highlight plaque, after which plaque and gingival indices were recorded. All the values were tabulated, and the data were evaluated using an independent t-test, paired t-test and ANCOVA. Results: On the last day of study, the area of visible plaque was significantly lower in the Cymenol Group in comparison with Listerine; the Cymenol mouthwash was found to have reduced the area of visible plaque. Conclusion: The use of Cymenol mouthwash as an anti-plaque agent is a valuable alternative to classical anti-plaque agents.